2006
DOI: 10.4067/s0716-078x2006000400008
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the photosynthetic performance of two evergreen Nothofagus species in south central Chile

Abstract: The evergreen Nothofagus dombeyi and Nothofagus nitida are important members of the temperate Chilean rainforest. They seldom grow together in nature. Nothofagus nitida is more susceptible to excess light and drought than N. dombeyi. We postulate that the different properties of the photosynthetic apparatus under common garden conditions of these species could explain their contrasting habitat preferences. The two species growing in a common garden in south central Chile were studied. The optimal photochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 36 publications
5
24
1
Order By: Relevance
“…(Mohammed et al, 2003) and therefore it can not be interpreted as photodamage, but as a regulatory adjustment of PSII efficiency (Huner et al 2002). In contrast, the evergreen Nothofagus dombeyi from the Chilean temperate rainforest showed a decrease in Fv/Fm in summer at the highest irradiances (midday) (Zúñiga et al 2006), but not in winter as was found in our study for L. ferruginea and E. coccineum. Because this decline was reversed in the afternoon in N. dombeyi, these authors suggested a photoprotective down regulation of the PSII mediated by Z, thus preventing the damage of the photosynthetic system as reported by other authors (Adams & Demmig-Adams 1994, Krause & Winter 1996.…”
Section: Chlorophyll and Total Carotenoid Contentscontrasting
confidence: 37%
See 3 more Smart Citations
“…(Mohammed et al, 2003) and therefore it can not be interpreted as photodamage, but as a regulatory adjustment of PSII efficiency (Huner et al 2002). In contrast, the evergreen Nothofagus dombeyi from the Chilean temperate rainforest showed a decrease in Fv/Fm in summer at the highest irradiances (midday) (Zúñiga et al 2006), but not in winter as was found in our study for L. ferruginea and E. coccineum. Because this decline was reversed in the afternoon in N. dombeyi, these authors suggested a photoprotective down regulation of the PSII mediated by Z, thus preventing the damage of the photosynthetic system as reported by other authors (Adams & Demmig-Adams 1994, Krause & Winter 1996.…”
Section: Chlorophyll and Total Carotenoid Contentscontrasting
confidence: 37%
“…There appears to be a high proportion of nocturnal retention of A+Z in these two Proteaceae, similar as has been found in N. nitida, a species from the Chilean temperate rainforest (Zúñiga et al 2006). Sustained retention of large amounts of A+Z appears to be a common response to low temperature stress under field conditions in plants (Adams & Demmig-Adams 1994, Adams & Barker 1998, Verhoeven et al 1999.…”
Section: Chlorophyll and Total Carotenoid Contentsmentioning
confidence: 74%
See 2 more Smart Citations
“…This capability could refer to changes in photosynthetic performance, in biomass compartmentalization, in gas exchange, in leaf morphology and in water capture (Sun et al, 1995;Evans and Poorter, 2001;Damesin, 2003;Reynolds and Frochot, 2003;Sardans et al, 2006;Lencinas et al, 2007;Martínez Pastur et al, 2007). These physiological adjustments could also modify nutrient tissue concentration and their requirements (Sardans et al, 2006), as well as leaf pigment changes in the seedlings (Valladares et al, 2000;Damesin, 2003;Larcher, 2003;Zúñiga et al, 2006;Lichtenthaler et al, 2007) according to the new micro-environmental conditions.…”
Section: Introductionmentioning
confidence: 93%